Manga from the Floating World: Comicbook Culture and the Kibyōshi of Edo Japan. - Kern, Adam (Harvard East Asian monographs, 2020)
"The first full-length study in English of the kibyōshi, a genre of woodblock-printed comicbook widely read in late eighteenth-century Japan that became an influential form of political satire. The volume is copiously illustrated with rare prints from Japanese archival collections"--Provided by publisher.